Understanding Thai and Myanmar Conflict Management Styles: A Cross-Cultural Dimension of Organization Development - Kyaw, Thiri; Pruetipibultham, Oranuch (ABAC ODI JOURNAL Vision. Action. Outcome, 2023)
Cross-cultural interactions have gained significant attention in recent years due to the tremendous business advancements and high collaboration among the diverse workforce. The medical tourism industry has become a global phenomenon (Chen & Wilson, 2013). Among the medical tourism destinations, Thailand is well-reputed for its competitive advantages; especially medical tourists from Myanmar and Cambodia in the ASEAN region highly contribute to the private international hospitals in Thailand and to the medical tourism industry there. Thai international hospitals employ Myanmar talents to provide required services to Myanmar medical tourists. According to Ting-Toomey and Oetzel (2001), more chances of work-related conflicts or difficulty are likely to occur among different cultural groups in the workplace. Therefore, there is a research gap in terms of investigating the conflict management style of Myanmar and Thai managerial staff working in Thai private international hospitals from a cross-cultural perspective. Semi-structured interviews were used in the present study to collect data from 30 Thai and Myanmar participants; a descriptive analysis was used to analyze the data; and the Rahim Organizational Conflict Inventory-II (Rahim, 1983) was referred to identify the conflict styles of the participants. As was seen in the study, Thais favored four conflict styles from the highest to lowest: dominating, integrating, compromising, and obliging, while Myanmar people preferred avoiding, dominating, and obliging. The findings of this study can be used as a contribution of knowledge to HROD scholars, practitioners, and organizations in Thailand in terms of the employment of Myanmar talents.